Map of Alaska and portions of the Northwest Territory, showing routes to the gold fields / Pool Bros - Poole Brothers (Poole Brothers, 1897)
Includes addresses of travel agents and 1 inset map: Key map showing routes to Alaska.; Includes ancillary descriptive text and maps: Map of Great Northern Railway Coast Lines and connections for Alaska, copyrighted, 1896, by F.L. Whitney -- Great Northern Railway and connections. This is a promotional map for The Great Northern Railway, seeking customers ready to join the Klondike Gold Rush. The map uses large red letters to label numerous fields of gold, oil and coal. Red, dashed lines suggest easy access to these areas via steamship and trains when in fact, passage to these interior lands was difficult. Few maps of the Yukon and Alaska existed when the gold rush hit. Many companies, such as the Poole Brothers of Chicago who prepared this map for the Great Northern Railway Company, rushed to create maps to meet demand. Accuracy and detail were often of little concern. Companies like the Great Northern Railway stood to make a fortune transporting Yukon-bound gold seekers. Such a map would be useless to a prospector. -ARC- Color 1:4,400,000